APPLICATION MACHINE DRYER MECHANICAL FORCED CONVECTION IN THE PROCESS OF DRYING CASSAVA CHIP - Retno Damayanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Implemented Mocaf flour processing on SMEs still has a weakness in the process of drying cassava chips.The drying process is using natural sun drying. In hot conditions in full sun drying takes 2 to 3 days while in the rainy season between November and April the SMEs unproductive because of the delay time of drying, the chip mocaf grow mushrooms with the consequences of the whole production must be discarded. Thus most of the cluster chose not to produce in the rainy season.Application of forced convectionmechanical dryer is an alternative of drying technology in the fermented cassava chips drying process due have a good quality and a longer storability. Forced convectionmechanical dryer is designed with indirect heating system consisting of a heat exchanger unit, the drying chamber, shelves, blower and frames. Cassava chips drying machine capacity is 40-80 kg/batch is divided into 80 shelves. Fuel is LPG. The results of machine performance test showed an effective drying cassava chips is 3.5 hours by the end of the temperature distribution between 31.9 to 47.6 ° C and a water content of 12.1 to 12.9%, with the desired optimum water content of the cassava chips for further processing into flour mocaf is 12-13%.